O efeito da suplementação aguda de suco de beterraba rico em NO3- no rendimento de corredores de rua - Santos, Paula Souza Alves dos (2022)
Supplementation of nitrate-rich beet juice (SSBN) has become a promising ergogenic resource for modalities whose characteristic is aerobic, as well as street running, in which many seek an improvement in performance. In this sense, the following research aimed to analyze whether the use of acute supplementation of beetroot juice, rich in nitrate, improves the aerobic performance of street runners in a track test. For this, the study had 13 men, aged between 25 ± 4.7 years old, engaged in street running in the city of Lavras-MG, with at least 18 months of practice. Participants underwent a randomized, placebo-controlled crossover. The study was followed by 2 stages, the first consisted of recruiting and signing the informed consent form, in addition to instructions for completing the 24-hour dietary recall. While the second stage was subdivided into 3 visits to the GEPREN-UFLA laboratory, the first moment being destined to the characterization, performing anthropometry and body composition, together with the collection of the 24-hour food recall. The second and third visits had 7 days of washout between them, where 2h after ingestion of beetroot juice supplementation rich in nitrate or placebo, the participants were submitted to a 3,200m time trial on the athletics track, recording time, subjective perception of effort and heart rate, variables such as speed, VO2peak, speed threshold, strategy behavior in two analysis configurations (every 25% and beginning (400m), middle (2400m) and final (400m) and macronutrient consumption were also analyzed. During the waiting period, blood pressure was measured every 30 minutes. Descriptive statistics, the Kolmogorov-Smirnov and Shapiro-Wilk tests were used to report sample normality and the Levene test for equality of variances (SPSS® 21.0 ).The values obtained in the 3,200m time trial, as in time, resulted in a faster conclusion after ingestion of SSBN (SUP: 720.0 ± 83.7 VS. PLA 722.6 ± 81.5s), in the configurations used rhythm, there was an increase in the 1st of 0.98% corresponding to the first 25% of the path, and 0.59% in the middle and 0.42% in the final 25%. The 2nd configuration shows an increase of 1.47% at the beginning and 1.05% at the end of the path. Thus, peak velocity (SUP 16.20 km/hr-1 ± 1.89, PLA 16.13 km/hr-1 ± 1.86), VO2peak (SUP 61.1 ml(kg.min)-¹ ± 6 ,6; PLA 60.9 ml(kg.min)-¹ ± 6.4), 2nd speed threshold ( SUP 15.95 ± 1.74 PLA 15.95 ± 1.69), subjective perception of exertion, frequency final heart rate and blood pressure with reductions at different times 60min (1.45%) and 90 min (4.48%) in diastole before the test and in systole after the test (1.86%) showed important responses, however these values did not show significance levels (p<0.05). The same for the individual analyzes of time with completion in up to 10.5s, increment of 1.54% in velocity, 1.38% in VO2peak and 1.46% in the 2nd velocity threshold. The macronutrients presented the following configuration for protein 1.60g/kg ±0.91, lipids 0.70 g/kg ± 0.64 and carbohydrate 3.97 g/kg ± 2.75. It can be concluded that the ingestion of acute nitrate-rich beetroot juice supplementation contributes to the magnitude point in a 3,200m time trial test, but does not demonstrate statistical differences in aerobic performance and variables.